Efecto del desestresante (admf) inyectado al pseudotallo sobre el rendimiento y sanidad del cultivo de plátano (musa aab) bajo riego deficitario - Camacho Peralta, Willian Gerardo (2014)
EL plantain (Musa AAB) now represents a culture of great economic interest, since it has good demand in the international market and it contributes to food security. Currently a total of 136,323 ha of which 74,815 ha are under monoculture system and 61,508 ha are associated with other crops are reported. Average yields reported in the country is 5 MT / ha / year which is relatively low. Low productivity is a result of biotic problems (Black Sigatoka, nematodes, black weevil, Virues etc.), abiotic (drought) and technological (low densities, lack of irrigation, proper nutrition, pest control, etc.). For the aforementioned reasons, it is necessary to use alternative technologies using bioestimulante of organic origin, to increase plant vigor, improve productivity, and lessen the stresses that occur at thedifferent stages. This work was conducted at the Experimental Station of Tropical Pichilingue lNlAP. The research aimed to help improve crop productivity of banana through the use of biotimulant products. It became necessary to establish paired adjacent parcels or where the treatment effect based ADMF vs. control without application was tested. In each plot, 25 plants were established, of which 9 plants were evaluated. The size of the samples used in the assay was 4 plots (n= 4) for the treatment and control ADMF base respectively. The treatment based on applied ADMF is injected pseudostem, the first was when the plants were 12 to 15 leaves, the second is taken after 15 days following issuance of bud (flowering stage) after the first harvest (R0), the application performs the pseudostem of the then newly harvested at (R1) before and after the issuance of the acorn (flowering stage) plants. Plant height (cm), pseudostem girth (cm), bunch weight (kg), functional leaf area (m2) and black Sigatoka index (%) were evaluated for comparison of means test was used “Student´s - paired t” to the significance level of p 0.05. The results showed statistically significant differences in the variables in the functional leaf area based ADMF treatment, resulting in a greater extension of the blade to photosynthetic activity. Also, was influenced the performance with 26 % more yield per hectare in the first cycle and 14 % in the second cycle of implementing the bioestimulante. The obtained effects are mainly attributed to the hormonal content of the product, which may potentiate the action of various metabolites in plants. The use of ADMF could become an alternative to improve the productivity of plantain, which would reduce the effect caused by abiotic stress